Empowerment Evaluation of Programs Involving Youth - Sarah Heath; Katherine Moreau (The Evaluation Center at Western Michigan University, 2022)
Background: Participatory and collaborative evaluation approaches, including Empowerment Evaluation (EE), are useful for evaluating programs involving youth. Empowerment evaluation involves stakeholders in the evaluation process through a set of structured steps. It is primarily concerned with empowering, illuminating, and building program beneficiaries' self-determination. Given the emphasis that EE places on inclusivity of stakeholders, it appears to be a good fit for evaluating programs that involve youth. Purpose: To explore the extent to which evaluators use EE to evaluate programs involving youth as well as what factor(s) facilitate and hinder their use of EE in these programs. Setting: The study involved evaluators associated with the Collaborative, Participatory and Empowerment Evaluation and Youth-Focused Evaluation Targeted Interest Groups (TIGs) of the American Evaluation Association (AEA) who are involved in evaluating programs targeted at youth. Intervention: Not applicable. Research Design: We used a two-phase sequential mixed-methods research design. In Phase 1, we surveyed evaluators. In Phase 2, we interviewed a sample of evaluators from Phase 1.  Findings: In Phase 1, 41 (53.9%) respondents indicated not using EE to evaluate programs involving youth, 30 (39.5%) had used EE and 5 (6.6%) were unsure. Of those who used EE, they used it to teach youth program stakeholders about evaluation (n=8, 24.2%), produce more authentic results by engaging youth as experts of their lived experience (n=7, 21.2%) or produce more useful results for stakeholders to use (n=6, 18.2%), as well as other less popular reasons. In Phase 2, 12 interviewees raised five factors that facilitate or hinder the use of EE to evaluate programs involving youth including, evaluator perceptions, type of evaluation experience, evaluator knowledge and professional training, guidelines from organizations and funders, and stakeholders and time. Factors that some interviewees viewed as facilitators others viewed as hinderances.   Keywords: empowerment evaluation, program evaluation, youth-focused evaluation